Flow control in Banki turbines. (October 2017) - Popescu, Daniela; Popescu, Constantin; Dragomirescu, Andrei
Abstract: Cross flow micro turbines are environmentally friendly equipment. A low head Banki turbine is studied in this paper numerically and experimentally in order to identify the reasons why the turbine efficiency is poor at low rotational speeds. A procedure that consists in dividing the flow domain into different zones is proposed for clarifying the main issues. The turbine efficiency obtained experimentally is explained based on a CFD analysis that highlights the influence of recirculation phenomena and shock losses produced when the water jet impinges on the shaft. This analysis is also used to propose a device for internal flow control.